Eosinophilic pustular folliculitis of infancy: A rare diagnosis in children - Anne Sofie Frølunde (Clinical Case Reports, 2021)
Abstract Remember EPFI as a differential diagnosis in children with a rash on the scalp and no effect of antibiotic treatment.